To whom can Canada be home? : an intersectional analysis of the perceived challenges in accessing housing for women asylum seekers in Montreal, Canada - Nantel, Mélina (2024)
This study examines the complex interplay between various identity factors such as gender, parenthood, and citizenship status, collectively influencing housing accessibility for asylum-seeking women in Montreal, Canada. By focusing on their understudied experiences, it addresses two key questions: (1) What are the perceived challenges faced by asylum-seeking women in accessing housing in Montreal? (2) How do intersecting social categories such as gender, race, socioeconomic class, immigration status, and parenthood collectively influence the housing accessibility of asylum-seeking women in Canada? This research is grounded in intersectionality theory, which offers a nuanced understanding of the intricate dynamics involved. Qualitative methodology is employed to amplify the voices of asylum-seeking women through semi-structured interviews, providing a platform for both structured questions and narrative storytelling. Thematic analysis and the matrix of domination inform data analysis. The main findings reveal logistical, economic, and social and cultural barriers faced by asylum-seeking women in accessing housing. These challenges necessitate the implementation of targeted policy interventions that address the structural, disciplinary, hegemonic, and interpersonal domains of power. Specifically, asylum-seeking women encounter difficulties in accessing childcare or schools, navigating a new environment, delays in the immigration process, overcrowding in shelters, absence of a credit record, high rental prices, discrimination by landlords, inadequate government support, financial limitations, emotional burdens, social isolation, gender-based insecurity, discrimination, language barriers, and trust issues. These challenges intersect with gender, race, socioeconomic class, immigration status and parenthood, underscoring the necessity for tailored interventions to address the distinctive housing needs of asylum-seeking women and inform policy discussions for more equitable housing policies. This research is significant in that it has the potential to illuminate the overlooked narratives of asylum-seeking women, thereby fostering a more inclusive discourse on housing accessibility and contributing to a more responsive housing policy landscape.